A Multi-Center Study of the Prevalence and Characteristics of Eosinophilic Phenotype and High IgE Levels Among Chinese Patients with Severe Asthma [Corrigendum] - Ko FWS; Wang JKL; Hui DSC; Chan JWM; Cheung PS; Yeung YC; Sin KM; Ip MSM (Journal of Asthma and Allergy, 2023)
Ko FWS, Wang JKL, Hui DSC, et al. J Asthma Allergy. 2023;16:173-182. The authors have advised there is an error in Table 1. Table 1 on Page 177, in the third-to-last row, data addressing Median (IQR) for Eosinophil count, cells/mm3 should read from 3.2 (1.7, 6.0) to 240.0 (110.0, 410.0). The authors apologize for this error. Correct Table 1: